Rodzina a wiara w Passio ss. Perpetuae et Felicitatis - Stawoska-Jundziłł, Bożena (Vox Patrum, 2018)
This article concerns about family thread in description of Perpetuae’s martyrdom in 3rd century Carthage. It describes Perpetuae’s family structure, family form upper strata of Roman Africa society, but not from aristocracy. The main function has father but almost equal in prestige is his daughter – Perpetua. Her husband was not mention text did not mention, except from the fact of being a father. Similar faint role have two living brothers. Story focus more on the youngest dead brother, that died in torment from deceased. Author suggest that Perpetua form unknown reason have advantage in prestige above her pagan father, implements, from her martyrdom, plan for salvation all of her family. This “altruistic” plan is to shorten posthumous torments for not baptise brother and to end members of family dilemma, torn between new religion and tradition. It makes Perpetua, a heroic person, that sacrifice upbringing of her child for the sake of rest family. This text’s meaning is rather exceptional for the early Christian literature and it definitely exclude authorship from Tertullian because of his view on women.